Calc03_9 - 29 ln u u d du a a a dx dx = → So far today we...

Info iconThis preview shows pages 1–11. Sign up to view the full content.

View Full Document Right Arrow Icon
3.9: Derivatives of Exponential and Logarithmic Functions Mt. Rushmore, South Dakota Greg Kelly, Hanford High School, Richland, Washington Photo by Vickie Kelly, 2007
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Look at the graph of x y e = The slope at x=0 appears to be 1. If we assume this to be true, then: 0 0 0 lim 1 h h e e h + - = definition of derivative
Background image of page 2
Now we attempt to find a general formula for the derivative of using the definition. x y e = ( 29 0 lim x h x x h d e e e dx h + - = 0 lim x h x h e e e h - = 0 1 lim h x h e e h - = 0 1 lim h x h e e h - = 1 x e = ⋅ x e = This is the slope at x=0, which we have assumed to be 1.
Background image of page 3

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
( 29 x x d e e dx =
Background image of page 4
x e is its own derivative! If we incorporate the chain rule: u u d du e e dx dx = We can now use this formula to find the derivative of x a
Background image of page 5

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
( 29 x d a dx ( 29 ln x a d e dx ( and are inverse functions.) x e ln x ( 29 ln x a d e dx ( 29 ln ln x a d e x a dx (chain rule)
Background image of page 6
( is a constant.) ln a ( 29 x d a dx ( 29 ln x a d e dx ( 29 ln x a d e dx ( 29 ln ln x a d e x a dx ln ln x a e a ln x a a Incorporating the chain rule:
Background image of page 7

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 8
Background image of page 9

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 10
Background image of page 11
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ( 29 ln u u d du a a a dx dx = → So far today we have: u u d du e e dx dx = ( 29 ln u u d du a a a dx dx = Now it is relatively easy to find the derivative of . ln x → ln y x = y e x = ( 29 ( 29 y d d e x dx dx = 1 y dy e dx = 1 y dy dx e = 1 ln d x dx x = 1 ln d du u dx u dx = → To find the derivative of a common log function, you could just use the change of base rule for logs: log d x dx ln ln10 d x dx = 1 ln ln10 d x dx = 1 1 ln10 x = ⋅ The formula for the derivative of a log of any base other than e is: 1 log ln a d du u dx u a dx = → u u d du e e dx dx = ( 29 ln u u d du a a a dx dx = 1 log ln a d du u dx u a dx = π 1 ln d du u dx u dx =...
View Full Document

This note was uploaded on 02/11/2011 for the course MAC 2233 taught by Professor Smith during the Spring '08 term at University of Florida.

Page1 / 11

Calc03_9 - 29 ln u u d du a a a dx dx = → So far today we...

This preview shows document pages 1 - 11. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online